India’s Export and Import Scenario of Natural Resins and Gums - Pal, Govind; Bhattacharya, A. (Indian Forester, 2013)
The study was carried out with a view to examine India’s export and import status of natural resins and gums, major destinations of export and major countries exporting to India. The study is based on secondary data collected for 10 years spanning from 1998-99 to 2007-08. The data were analyzed by using exponential function and instability index. The average annual exported quantity of all natural resins and gums during last 10 years was 1,49,652.96 tons valued 89,901.10 lakh while average annual imported quantity was 39,009.51 tons valued 15,682.70 lakh. The compound annual growth rate of natural resins and gums export during the reported period was positive for both quantity (7.85 per cent per annum) and value (6.96 per cent). The growth rate was also positive in natural resins and gums import and it was 20.77 and 30.05 per cent in quantity and value, respectively. The major export destination of Indian natural resins and gums were USA, China and Germany while major countries exporting to India were Afghanistan, Indonesia and China.